Total and size-resolved particle number and black carbon concentrations in urban areas near Schiphol airport (the Netherlands). (March 2015) - Keuken, M.P.; Moerman, M.; Zandveld, P.; Henzing, J.S.; Hoek, G.
Abstract: The presence of black carbon, and size-resolved and total particle number concentrations (PNC) were investigated in the vicinity of Schiphol airport in the Netherlands, the fourth busiest airport in Europe. Continuous measurements were conducted between March and May 2014 at Adamse Bos, located 7 km from Schiphol, and in 2012 at Cabauw, a regional background site 40 km south of Schiphol. No significantly elevated black carbon levels were found near Schiphol. However, PNC increased during periods in which the wind direction was from Schiphol: at Cabauw by 20% and at Adamse Bos by a factor of three, from 14, 100 (other wind directions) to 42, 000 # cm −3 between 06.00 and 23.00. The size distribution of Schiphol-related PNC was dominated by ultrafine particles, ranging from 10 to 20 nm. Four relevant particle number (PN) emission sources at Schiphol were identified as being responsible for the elevated PNC levels at Adamse Bos: take-off and climb-out on the Kaagbaan and Aalsmeerbaan runways, planes waiting at the gates, and landing on the Buitenveldertbaan runway. PN emissions from road traffic at and near the airport were less important than air traffic. The exposure to Schiphol-related PNC in urban areas northeast of Schiphol in Amsterdam and Amstelveen was estimated for 2012 using a Gaussian Plume model. The results showed that a considerable number of the 555, 000 addresses in the modelling domain were exposed to elevated PNC. For example: 45, 000 addresses suffered long-term exposure to an additional annual background PNC of 5–10, 000 # cm −3 originating from Schiphol and 60, 000 addresses suffered short-term exposure (14% of the time) of additional 10–15, 000 # cm −3 originating from Schiphol. Further research on emission sources and the dispersion of PN is recommended and may support future studies on eventual health effects. Highlights: Ultrafine particles are a factor 3 elevated 7 km downwind Schiphol airport. The size-distribution of these particles is dominated by particles of 10–20 nm. 45, 000/60, 000 addresses exposed to 5–10, 000 (annual)/10–20, 000 (hourly) #/cm 3 .